Disasters: Spatio-Temporal Distribution of Dhankuta District, Nepal - Linkha, Tika Ram (Rupantaran: A Multidisciplinary Journal, 2020)
This paper attempts to analyze the temporal and spatial distribution of disaster in Dhanktua district, Nepal. It provides information regarding when and where the disasters have mostly occurred in Dhankuta. Disaster can occur at any time at anywhere although every disaster has a temporal and spatial dimension which helps to predict the future events In this context, this paper provides the history and trend of disasters in Dhankuta. This paper is based on mostly secondary data extracted from the Ministry of Home Affairs, Disaster Risk Reduction (DRR) Portal. To analyze this, mostly descriptive methods has been applied where the quantitative method also applied for the reflection of disaster data. Fire, landslide, heavy rainfall and thunderbolt were the major disasters that frequently occurred in this district during 2017-2019. It is found that fire incidents were frequently occurred in the month of March, the landslide in July, heavy rainfall in July and thunderbolt in April. It is interesting that, those years where the incidents of fire were higher the incidents of the landslide were low and vice versa and there is a positive relationship between landslide and heavy rainfall. This study will important to local levels and relevant agencies for disaster preparedness because the impact of the disaster is based on the level of preparedness. This analysis is based on limited data which covered 10 March 2017 to 31 December 2019. This study provides a new perspective in the field of disaster where temporal and spatial dimensions are considered.